Aetiologies and temporal trends of atrioventricular block in young patients: a 20-year nationwide study. Issue 11 (19th August 2019) - Rudbeck-Resdal, Johnni; Christiansen, Morten K; Johansen, Jens B; Nielsen, Jens C; Bundgaard, Henning; Jensen, Henrik K
Abstract: Aims: To describe aetiologies and temporal trends in young patients with atrioventricular block (AVB). Methods and results: We identified all patients in Denmark, receiving their first pacemaker because of AVB before the age of 50 years between 1996 and 2015. Medical records were reviewed and clinical information and diagnostic work-up results were obtained to evaluate the aetiology. We used Poisson regression testing for temporal trends. One thousand and twenty-seven patients were identified, median age at time of implantation was 38 (interquartile range 25–45) years, 584 (56.9%) were male. The aetiologies were complications to cardiac surgery [ n  = 157 (15.3%)], congenital AVB [ n  = 93 (9.0%)], cardioinhibitory reflex [ n  = 52 (5.0%)], congenital heart disease [ n  = 43 (4.2%)], complication to radiofrequency ablation [ n  = 35 (3.4%)], cardiomyopathy [ n  = 31 (3.0%)], endocarditis [ n  = 18 (1.7%)], muscular dystrophy [ n  = 14 (1.4%)], ischaemic heart disease [ n  = 14 (1.4%)], sarcoidosis [ n  = 11 (1.1%)], borreliosis [ n  = 9 (0.9%)], hereditary [ n  = 6 (0.6%)], side-effect to antiarrhythmics [ n  = 6 (0.6%)], planned His-ablation [ n  = 5 (0.5%)], complication to alcohol septal ablation [ n  = 5 (0.5%)], and other known aetiologies [ n  = 11 (1.1%)]. The aetiology remained unknown in 517 (50.3%) cases. While the number of patients with unknown aetiology increased during the study period ( P  < 0.001), we observed no significant change in the number of patients with identified aetiology ( P  = 0.35). Conclusion: In a nationwide cohort, the aetiology of AVB was identified in only half the patients younger than 50 years referred for first-time pacemaker implantation. The number of patients with unknown aetiology increased during the study period. These findings indicate need for better insight into aetiologies of AVB and improved diagnostic work-up guidelines.